Online Green Purchase Intention in the North Macroregion of Peru: The Moderating Role of Customer Behavioral Aspects - Lamadrid Aldana, Milagros; GUZMÁN VALLE, MARÍA DE LOS ÁNGELES; Acosta Enriquez, Benicio Gonzalo; Rocero Salazar, Cesar Ricardo; Li Vega, Fiorella Vanessa; Alburuqueque Arana, Fausta Elizabeth; Flores Lezama, Marilú Trinidad (LACCEI, 2024)
The present study investigated the antecedents of online ecological purchase intention considering the impact of electronic service quality and several customer behavioral aspects: ecological word-of-mouth marketing, ecological trust, ecological greenwashing, consumer social responsibility, perceived ecological value, and ecological consumer involvement. Nonprobabilistic samples of 392 respondents from three provinces in the Lambayeque region were collected using a questionnaire. The data were analyzed using partial least squares with the structural equation model. The results show that the quality of electronic services has a significant positive impact on purchase intention. Furthermore, they show that only ecological word-of-mouth marketing positively moderates the relationship between electronic service quality and purchase intention. The results can improve the understanding of Lambayecan consumers' ecological product buying behavior in relation to the electronic service quality provided by companies.